Taiwan's economic transformation leadership, property rights and institutional change : 1949-1965 - Kuo, Tai-Chun, 1952-; Myers, Ramon Hawley, 1929-; ProQuest (Firm) (London ; New York : Routledge, 2012)
"This book charts the period before Taiwan's post-war economic miracle took hold (1949-1965) and proffers that it was the Kuomintang Government's endorsement of property rights reform and institutional change that enabled Taiwan to transform from an impoverished command economy to a market-based economy, which in turn led to Taiwan becoming one of the fastest growing economies in the world. Using first-hand interview material with key government officials from the period, and analysis of hitherto unused Chinese-language archives, this book is empirically very rich. It also gives the reader insights into Taiwan's developmental experience and the direction in which, under different circumstances, China's post-war development might have proceeded. Taiwan's Economic Transition will be an invaluable resource for anyone interested in the economic and political history and development of Taiwan. More broadly it will also appeal to scholars and students of China's historical and contemporary development"--
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Capitalism -- Taiwan; Taiwan -- Economic policy -- 1945-1975.; Taiwan -- Economic conditions -- 1945-1975.; Electronic books